2020
DOI: 10.7717/peerj.10481
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of ischaemia/ hypoxia on angiogenesis in rat myofascial trigger points using colour Doppler flow imaging

Abstract: Background & Aims Myofascial pain syndrome (MPS) is a common non-articular disorder of the musculoskeletal system that is characterized by the presence of myofascial trigger points (MTrPs). Despite the high prevalence of MPS, its pathogenesis, which induces the onset and maintenance of MTrPs, is still not completely understood. To date, no studies have investigated the changes in the biochemical milieu caused by ischaemia/hypoxia in the MTrP regions of muscle that are proposed in the integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…6 ). These results are consistent with those of previous studies on stiffness ( Jiang et al, 2020 ; Liang, Guo & Li, 2021 ). Those studies confirmed that the stiffness of MTrPs tissue or the surrounding tissue is greater than that of normal tissue from the same location.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…6 ). These results are consistent with those of previous studies on stiffness ( Jiang et al, 2020 ; Liang, Guo & Li, 2021 ). Those studies confirmed that the stiffness of MTrPs tissue or the surrounding tissue is greater than that of normal tissue from the same location.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, there is a high demand for imaging techniques that provide quantitative and objective measurements for tense belts and MTrPs. Magnetic resonance imaging (MRI) and ultrasound (US) have been used to identify MTrPs for diagnosis and treatment evaluation ( Jiang et al, 2020 ; Liang, Guo & Li, 2021 ; Sikdar et al, 2009 ; Yu et al, 2021 ). Although both are noninvasive examination techniques, US has faster data acquisition and a lower cost than MRI.…”
Section: Introductionmentioning
confidence: 99%
“…In studies regarding the influence of NSAIDs on VEGF, it was demonstrated that NSAIDs could block the suppression of VEGF [ 46 , 47 ], which is in line with our research. Based on the latest reports from Jiang et al [ 48 ], who showed higher HIF-1α and VEGF concentrations in rats with active trigger points compared to control rats, we suggest that the tendency to lower VEGF after manual therapy, measured in our patients, might indicate a lower hypoxia occurrence [ 11 ].…”
Section: Discussionmentioning
confidence: 60%
“… 21 It was proposed that MTrPs may represent an ischemia-induced inflammatory microenvironment. 22 , 23 MRI-based measurements of cerebral edema, synovitis and tendinopathy have been suggested to correlate with inflammatory cytokines in previous findings. 24–26 Taking a lead from the above-mentioned studies, we hypothesize that the active MTrPs should generate changes on DTI indices and T2 values, which may reflect an inflammatory process at the level of MTrPs.…”
Section: Introductionmentioning
confidence: 79%
“…Data were collected as previously described by Fangyan Jiang. 23 Since this study requires post-mortem elements at high cost, all efforts were made to minimize the number of animals sacrificed based on common sense to choose a suitable sample size. A total of 25 male Sprague-Dawley rats weighing 200–220g were obtained from the Animal Experiment Center of Guangxi Medical University (Nanning, China) and were 7 weeks old at the start of experiments.…”
Section: Methodsmentioning
confidence: 99%